“PAH” carcinogens; what nullified early warnings - Greenberg, Morris (European Journal of Oncology and Environmental Health, 2009)
The carcinogenic effects of soot were recognized some 300 years ago and it was conjectured that the responsible agent was a volatile fraction. Identification of a specific chemical agent was not required for the appropriate intervention to be determined, nevertheless its implementation was delayed by political considerations. Awareness that work other than chimney cleaning was associated with excess cancer mortality followed: they had in common exposure to carcinogenic “PAHs”. In none of these exposures (coal distillation products including tars, pitch, asphalt, mineral oils, shale oil, metal working fluids) was intervention promptly legislated for that effectively eradicated the risks. The application of the Industrial Hygiene Measures of Containment and Personal Protection have provided limited protection, as the Substitution. Despite the development of a more compassionate national political philosophy, and the determination of the precise chemical agents that are the most potent carcinogens, industry has learnt how, by the employment of public relation experts and the commissioning of sympathetic scientists, its interests can be protected.